2008
DOI: 10.1002/cphc.200700648
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Heteroleptic Iridium Complexes Containing Carbazole‐Functionalized β‐Diketonates

Abstract: Twelve iridium complexes with general formula of Ir(C;N)(2)(LX) [C;N represents the cyclometalated ligand, i.e. 2-(2,4-difluorophenyl) pyridine (dfppy), 2-phenylpyridine (ppy), dibenzo{f, h}quinoxaline (DBQ); LX stands for beta-diketonate, i.e. acetyl acetonate (acac), 1-(carbazol-9-yl)-5,5-dimethylhexane-2,4-diketonate (CBDK), 1-(carbazol-9-yl)-5,5,6,6,7,7,7-heptafluoroheptane-2,4-diketonate (CHFDK), 1-(N-ethyl-carbazol-3-yl)-4,4,5,5,6,6,6-heptafluorohexane-1,3-diketonate (ECHFDK)] are synthesized, characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…We reported the synthesis, photophysical, and electrochemical properties of a series of iridium complexes with different b-diketonates with a range of triplet energy levels as the ancillary ligand. [29] The effect of the triplet energy level of b-diketonates on the properties of iridium complexes was examined. Strong …”
Section: Research Newsmentioning
confidence: 99%
“…We reported the synthesis, photophysical, and electrochemical properties of a series of iridium complexes with different b-diketonates with a range of triplet energy levels as the ancillary ligand. [29] The effect of the triplet energy level of b-diketonates on the properties of iridium complexes was examined. Strong …”
Section: Research Newsmentioning
confidence: 99%
“…The computations also suggest that the phosphorescent emission wavelengths could be blue-shifted by introducing π electron-withdrawing groups and by suppressing the π-conjugation in the C^N ligand. Liu et al (2008) also investigated the photophysical properties of heteroleptic iridium complexes containing carbazole-functionalized β-diketonates. The authors have studied the influence of the triplet energy level of the ancillary carbazole-containing ligand on the photophysical and electrochemical behavior, and found that the superposition of the state density map of the triplet energy levels between the β-diketonate and the Ir(C^N) 2 fragment is the key factor to obtain strong 3 LC or 3 MLCT-based phosphorescence and high photophysical performance.…”
Section: Introduction Of Novel Ligandsmentioning
confidence: 99%
“…For background to organic light-emitting diodes based on phosphorescent complexes, see: Baldo et al (1998Baldo et al ( , 2000; Hwang et al (2005); Liu et al (2008); Tsuboyama et al (2003). For the synthesis, see: Zhang et al (2003Zhang et al ( , 2005.…”
Section: Related Literaturementioning
confidence: 98%
“…In recent decades, organic light-emitting diodes (OLEDs) based on phosphorescent complexes have attracted increasing attention due to their potential applications in full-color flat panel displays (Baldo et al, 1998(Baldo et al, , 2000. Among these phosphorescent complexes, iridium cyclometalates often exhibit favorable photoproperties for OLEDs including short phosphorescent lifetimes, high quantum efficiencies and good stability (Liu et al, 2008;Hwang et al, 2005;Tsuboyama et al, 2003). Zhang et al (2005) demonstrated a high efficiency yellow OLED using [Ir(mdpp) 2 (acac)] [mdpp = 2-(5-methyl-3-phenylpyrazine-2-yl)phenyl, Hacac = acetylacetone] as the dopant.…”
Section: Data Collectionmentioning
confidence: 99%